Innovation without patents: harnessing the creative spirit in a diverse world - Ana Maria Carneiro; Sergio Salles-Filho (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
Cheltenham, UK: Edward Elgar, 2007 ISBN: 978-184542959-1